Coherent control of anisotropic SPPs in a symmetric double-layer metal/uniaxial dielectric structure - Jabir Khan; Amjad Sohail; Amsyar Rahim; Muhammad Shafiq; Hazrat Ali; Saeed Haddadi (Scientific Reports)
Abstract We investigate the coherent control of anisotropic surface plasmon polaritons (SPPs) in a symmetric double-layer metal/uniaxial dielectric structure. The directional anisotropy introduced by the uniaxial dielectric enables tunable SPP dispersion, absorption, and propagation characteristics through an external control field. We analyze reflection and transmission spectra, dispersion relations, propagation lengths, and the scattering matrix eigenmodes. Our results reveal strong modulation of SPP wavelength and enhanced propagation length with varying control field strength and metal layer composition. Remarkably, we observe coherent perfect absorption for both symmetric and anti-symmetric modes, an effect not commonly realized in such layered anisotropic systems. This work introduces a novel platform for actively tunable nanoplasmonic devices, with potential applications in waveguiding, sensing, and plasmonic circuitry.